2011
DOI: 10.1039/c1em10150a
|View full text |Cite
|
Sign up to set email alerts
|

Tracking sewage derived contamination in riverine settings by analysis of synthetic surfactants

Abstract: A study has been made of the presence and reactivity of the most commonly used surfactants, both anionic (linear alkylbenzene sulfonates, LAS, and alkyl ethoxysulfates, AES) and non-ionic (alcohol polyethoxylates, AEOs, and nonylphenol polyethoxylates, NPEOs), in water and surface sediments from the middle stretch of the Guadalete River in SW Spain (12 stations). Average values were between 0.1 and 3.7 mg kg À1 in sediment, and between 0.2 and 37 mg L À1 in water. The sorption of surfactants was dominated by h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
24
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(31 citation statements)
references
References 41 publications
6
24
0
Order By: Relevance
“…Sewage effluents may contain surfactant concentrations up to 872 μg/L for LAS , and from 0.9 to 15.6 μg/L for NPEOs and AEOs (Loyo-Rosales et al, 2007;Morrall et al, 2006). A considerable number of studies have also reported the presence of LAS (Corada-Fernández et al, 2011;Ding et al, 1999;Eichhorn et al, 2002;González-Mazo et al, 1998;Lara-Martín et al, 2008;León et al, 2002;Marcomini et al, 2000) and NPEOs (Belmont et al, 2006;Corada-Fernández et al, 2011;Isobe and Takada, 2004;Jonkers et al, 2003Jonkers et al, , 2005Lara-Martín et al, 2008;Lee Ferguson et al, 2001;Maruyama et al, 2000;Petrovic et al, 2002;Zoller, 2006;Zoller and Hushan, 2000) in surface waters all around the world, with values between b50 and N1000 μg/L and between b0.1 and 100 μg/L, respectively. Data on the occurrence of AEOs are more limited in spite of their production volumes being comparable to those for LAS and NPEOs.…”
Section: Introductionmentioning
confidence: 94%
“…Sewage effluents may contain surfactant concentrations up to 872 μg/L for LAS , and from 0.9 to 15.6 μg/L for NPEOs and AEOs (Loyo-Rosales et al, 2007;Morrall et al, 2006). A considerable number of studies have also reported the presence of LAS (Corada-Fernández et al, 2011;Ding et al, 1999;Eichhorn et al, 2002;González-Mazo et al, 1998;Lara-Martín et al, 2008;León et al, 2002;Marcomini et al, 2000) and NPEOs (Belmont et al, 2006;Corada-Fernández et al, 2011;Isobe and Takada, 2004;Jonkers et al, 2003Jonkers et al, , 2005Lara-Martín et al, 2008;Lee Ferguson et al, 2001;Maruyama et al, 2000;Petrovic et al, 2002;Zoller, 2006;Zoller and Hushan, 2000) in surface waters all around the world, with values between b50 and N1000 μg/L and between b0.1 and 100 μg/L, respectively. Data on the occurrence of AEOs are more limited in spite of their production volumes being comparable to those for LAS and NPEOs.…”
Section: Introductionmentioning
confidence: 94%
“…Any environmental compartment (surface waters, sediment, biota…) is susceptible of being contaminated by these compounds and/or their degradation metabolites [2,28]. As example, a considerable number of studies have reported the presence of LAS in surface waters [29][30][31] at levels typically ranging from less than 1 ng/L to several hundreds of µg/L respectively, depending on the distance from urban wastewater discharge sources and the type of wastewater treatment. Available studies about the presence, environmental behavior and distribution of non-ionic surfactants are mainly focused on NPEOs (nonylphenol polyethoxylates, which are the major fraction of APEOs).…”
Section: Introductionmentioning
confidence: 99%
“…Available data concerning to the presence of aliphatic anionic (AES) and nonionic (AEOs) surfactants, as well as cationic surfactants of any class, are rather limited. There are only a few papers about the occurrence of AEOs [36,40,43,44] and AES [19,31] in sediments, showing levels ranging from <0.1 to 23 mg/kg. Some authors have also measured concentrations between <0.1 and 72 µg/L for AES [19,31] and AEOs [36,40,43] in surface waters.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations